Organization and Work of the Čačak County Court in the 1840s - Popović, Miroslav M.; Miličić, Kristina R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The aim of the paper is to present the organization and work of the Čačak County Court in the 1840s. The source material used for the paper are the reports of the Ministry of Justice, with statistical data, and lists of officials with information about employees, as well as published official state data and the List of ax heads, municipalities and conciliation courts in the Principality of Serbia from 1839. Also, a comparison will be made in relation to other county courts in the country during the observed period. Basic data will be presented on the costs that were determined for this court and the amounts that were deposited within this court, as well as those that were kept in the name of the assets of persons under guardianship (so-called pupilar masses).
Keywords: Principality of Serbia; judiciary; statistics; County Court of Čačak